Aseptic HLA B27-positive spondylodiscitis: decreased 18F-FDG uptake after etanercept treatment - M. Benucci; A. Damiani; A. Arena; M. Infantino; M. Manfredi; F. Li Gobbi (PAGEPress Publications, 2016)
We observed a 69-year old man suffering from HLA B27 ankylosing spondylitis with persistent night back pain. 18F-FDG-PET/CT showed an increased metabolism at the level of the spinal space of L2-L3, L3-L4 with increased uptake compatible with spondylodiscitis. He started therapy with etanercept 50 mg/week. After six months of treatment repeated testing showed no uptake of the discs and vertebral bodies.